The aphidophagous predator Harmonia axyridis (Coleoptera: Coccinellidae) in Greece, 1994-1999 - Dimitrios C. KONTODIMAS; George J. STATHAS; Aggeliki F. MARTINOU (European Journal of Entomology, 2008)
During the years 1994-1999, several hundreds of thousands of H. axyridis adults were released at various cultivations infested by aphids (citrus, vegetable and bean crops, maize etc.) and on ornamental plants in urban settings in central and southern Greece (mainly Attica and Peloponessos region) as well as on several islands. Between 1995-1999, spring sampling was conducted in some areas, just prior to releases, in order to determine if H. axyridis overwintered in the field. No presence of H. axyridis was recorded in any of the orchards where the predator had been released save in spring of 1998 and 1999 when small colonies (<50 individuals) of overwintered H. axyridis adults were observed in the Attica region. The above results suggest an inability of released H. axyridis populations to establish in Greece, although in some areas this species became an important biocontrol agent during the growing season.